1993
DOI: 10.2307/1131262
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Gender Boundaries in Preadolescence: Contemporary Correlates and Antecedents of Boundary Violation and Maintenance

Abstract: Previous research has established the importance of gender boundaries as a normative aspect of development in middle childhood. Here, the nature and importance of gender boundaries as an individual differences construct was explored. Ratings of gender boundary violation and gender boundary maintenance were made of 47 10-11-year-old children participating in a series of summer day camps. These ratings were supported by videotape-based behavior codings of gender boundary violating behaviors and by live observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 0 publications
3
59
0
Order By: Relevance
“…This finding is consistent with existing literature on the maladaptive correlates and outcomes of childhood parentification (Carlson, Jacobvitz, & Sroufe, 1995;Jacobvitz, Hazen, Curran, & Hitchens, 2004). To that end, the present study suggests that, among a college sample of emerging adults, parentification is consistent with other forms of boundary dissolution in its negative association with interpersonal functioning (Collins et al, 1997;Fullinwider-Bush & Jacobvitz, 1993;Sroufe et al, 1993;Valleau et al, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with existing literature on the maladaptive correlates and outcomes of childhood parentification (Carlson, Jacobvitz, & Sroufe, 1995;Jacobvitz, Hazen, Curran, & Hitchens, 2004). To that end, the present study suggests that, among a college sample of emerging adults, parentification is consistent with other forms of boundary dissolution in its negative association with interpersonal functioning (Collins et al, 1997;Fullinwider-Bush & Jacobvitz, 1993;Sroufe et al, 1993;Valleau et al, 1995).…”
Section: Discussionsupporting
confidence: 92%
“…Previous research has shown that girls do not extend their playgroups to include girls who are not using cooperative methods of play (Fabes, Shepard, Guthrie, & Martin, 1997). Children who act in a cross‐gender fashion and cannot adjust their behavior for their same‐sex peer group may be ignored by peers (Fagot, 1977) or forced to play with the opposite sex, which is often associated with negative outcomes (Sroufe, Bennett, Englund, Urban, & Shulman, 1993). Generally, children who act in ways normative for the opposite sex experience negative social consequences (Crick, 1997), and our results extend these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Because gender is a salient social category in children's lives and forms the basis for intergroup biases and for selecting interaction partners (Martin et al., ; Powlishta, Serbin, Doyle, & White, ; Sroufe, Bennett, Englund, Urban, & Shulman, ), we focused on expectancies of gendered interactions. Specifically, our interest was in the early development of expectancies of inclusion and enjoyment and expectancies of social costs (i.e., social exclusion and rejection) that might occur in gendered contexts (own‐ and other‐gender interactions).…”
Section: Children's Cognitions About Social Interactionsmentioning
confidence: 99%